Associations between axial length, corneal refractive power and lens thickness in children and adolescents: The Ural children eye study: original article - Bikbov, Mukharram; Kazakbaeva, Gyulli M.; Fakhretdinova, Albina A.; Tuliakova, Azaliia M.; Iakupova, Ellina M.; Panda-Jonas, Songhomitra; Gilemzianova, Leisan I.; Garipova, Liana A.; Khakimov, Dinar A.; Islamova, Liaisan I.; Pokhilko, Nikolay I.; Jonas, Jost B. (Acta ophthalmologica, 2024)
Purpose To assess relationships between ocular biometric parameters in dependence of age and sex in children and adolescents. Methods In the Ural Children Eye Study, a school-based cohort study, 4933 children underwent an ophthalmological and general examination. Results Complete biometric measurements were available for 4406 (89.3%) children. Cycloplegic refractive error (mean: −0.87 ± 1.73 diopters (D); median: −0.38 D; range: −19.75 D to +11.25 D) increased (multivariable analysis; r2 = 0.73) with shorter axial length (β: −0.99; non-standardized regression coefficient B: −1.64; 95% CI: −1.68, −1.59) and lower corneal refractive power (β: −0.55; B: −0.67; 95% CI: −0.70, −0.64), in addition to higher cylindrical refractive error (β: 0.10; B: 0.34; 95% CI: 0.27, 0.41), thinner lens (β: −0.11; −0.85; 95% CI: −1.02, −0.69) and male sex (β: 0.15; B: 0.50; 95% CI: 0.42, 0.57). In univariate analysis, decrease in refractive error with older age was more significant (β: −0.38 vs. β: −0.25) and steeper (B: −0.22 (95% CI: −0.24, −0.20) vs. B: −0.13 (95% CI: −0.15, −0.11)) in girls than boys, particularly for an age of 11+ years. Axial length increased with older age (steeper for age <11 years) (B: 0.22 (95% CI: 0.18, 0.25) vs. 0.07 (95% CI: 0.05, 0.09)). In multivariable analysis, axial length increased with lower refractive error (β: −0.77; B: −0.42; 95% CI: −0.43, −0.40) and lower corneal refractive power (β: −0.54; B: −0.39; 95% CI: −0.41, −0.38), in addition to older age (β: 0.04; B: 0.02; 95% CI: 0.01, 0.03), male sex (β: 0.13; B: 0.23; 95% CI: 0.21, 0.32), higher cylindrical refractive error (β: 0.05; B: 0.09; 95% CI: 0.05, 0.14) and thinner lens (β: −0.14; B: −0.62; 95% CI: −0.72, −0.51). The axial length/corneal curvature (AL/CR) ratio increased until the age of 14 years (β: 0.34; B: 0.017; 95% CI: 0.016, 0.019; p < 0001), and then became independent of age. The AL/CR ratio increased (r2 = 0.78) mostly with higher corneal refractive power (β: 0.25; B: 0.02; 95% CI: 0.02, 0.02; p < 0.001), lower refractive error (β: −0.75; B: −0.05; 95% CI: −0.05, −0.05; p < 0.001), thinner lens thickness (β: −01.6; B: −0.09; 95% CI: −0.10, −0.08; p < 0.001) and older age (β: 0.16; B: 0.006; 95% CI: 0.005, 0.007; p < 0.001). Conclusions In this multiethnic group of school children in Russia, the age-related increase in myopic refractive error was more significant and steeper in girls, particularly for the age group of 11+ years. Determinants of higher myopic refractive error were longer axial length, higher corneal refractive power, lower cylindrical refractive error, thicker lens and female sex.